Potential for expanded application of endoscopic hand suturing: A pilot study of 15 cases - Kazutoshi Higuchi; Osamu Goto; Eriko Koizumi; Shun Nakagome; Tsugumi Habu; Yumiko Ishikawa; Kumiko Kirita; Hiroto Noda; Takeshi Onda; Jun Omori; Naohiko Akimoto; Katsuhiko Iwakiri (Endoscopy International Open, 2024)
Endoscopic hand suturing (EHS) was first developed to firmly close a mucosal defect following endoscopic submucosal dissection and has the potential for expanded applications. This study aimed to investigate the feasibility and safety of EHS in various clinical settings. In this single-center pilot study, 15 patients who had diseases with potential indications for EHS were prospectively recruited. Technical success, clinical success after the procedure, and severe EHS-related adverse events (AEs) were evaluated. EHS was applied for defect closure after gastric subepithelial lesion removal under laparoscopic observation (n = 9), defect closure after rectal endoscopic full-thickness resection (EFTR) (n = 2), defect closure after thoracoscopy-assisted esophageal EFTR (n = 1), mucosal closure for gastric ulcer bleeding (n = 1), mucosal closure after peroral endoscopic myotomy (POEM) (n = 1), and postoperative anastomotic leak (n = 1). EHS was completed without severe AEs and the clinical courses were also favorable in 13 patients (87%). The median suturing time was 61 minutes. In patients with POEM and anastomotic leak, EHS was discontinued because of the narrow lumen. In conclusion, EHS appears feasible and safe in situations.